Nuclear.Energy-Economic Growth Nexus in OECD Countries: A Panel Data Analysis - Ozcan, Burcu; Ari, Ayse (Inforum Verlags-Verwaltungsgesellschaft Mbh, 2016)
[Abstract Not Available]
Keywords: Energy-Consumption; Causal Relationship; Carbon Emissions; Cointegration; Oil; Inference; Income; Tests; Power; Gdp